Bacteriological Study of Ballast Water at Tanjung Emas Port, Semarang - Husna El Iksiroh; Sutrisno Anggoro; Henna Rya Abdurachim; Subagiyo Subagiyo; Mostafa Imhmed Ighwerb (Marine Science Department Diponegoro University, 2022)
The D-2 Ballast Water Management Convention standard regulates the requirements for the disposal of ballast water, which must not contain pathogenic bacteria, which are harmful to health and pollute the environment and the sustainability of local ecosystems. Tanjung Emas was chosen because it is one of the busiest ports in Indonesia to serve domestic shipping. In addition, there has never been a study examining the composition of bacteria carried through ballast water at the port of Tanjung Emas. This study aims to determine the content of pathogenic bacteria carried by the ballast water of ships docked at Tanjung Emas Port compared to the waters around the disposal and river flows around Tanjung Emas Port, Semarang. The samples were taken from 4 ships, 5 waters, and 2 rivers in Tanjung Emas area. The samples were analyzed biochemically to obtain the morphology of the bacteria present. The results showed that ballast water from the ships (KVOG, KMPS, and M) contains pathogenic bacteria: V. cholerae, E. coli, enterococci, S. typhii, S. desenteriae, Klebsiella, S. epidermidis, B. subtilis, and Actinobacteria. All types of that bacteria were also found in the Tanjung Emas waters except Actinobacteria. For three bacteria i.e. V. cholerae, E. coli, and enterococci whose levels exceed the threshold required by the BWM Convention and have the potential to pollute the Tanjung Emas environment. The water from the river did not contribute to the presence of V. cholerae bacteria in port waters, so the ballast water must be treated before being disposed of.